IMPLEMENTASI KOMPETENSI PUSTAKAWAN PADA DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI SULAWESI TENGGARA - BJ Herisman Saputra; La Ode Mustafa R; Erni Qomariah (Halu Oleo University, 2022)
This study aims to determine and analyze the implementation of librarian competencies at the Southeast Sulawesi Provincial Library and Archives Service. The approach in this study is a qualitative descriptive approach with 7 informants selected using purposive sampling technique. The data in this study were obtained through interviews, observation and documentation studies, the data obtained were then analyzed qualitatively with an interactive model consisting of data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of librarian competence is a review of the work abilities possessed by employees at the Southeast Sulawesi Provincial Library and Archives Service in carrying out their duties, roles and responsibilities. not yet fully good, where there are still many elements of competence that are not fully owned by librarians, whether in the form of competence in management, development, organization, information services, information technology, research as well as communication and interpersonal skills. Therefore, there is a need for more improvement in the competence of librarians.